Perbandingan Kelimpahan Larva Chironomidae di Dua Danau Berbeda di Provinsi Jambi - Siti Anindita Farhani; Yusli Wardiatno; Majariana Krisanti (Institut Pertanian Bogor, 2014)
This research was conducted at two different lakes in Jambi Province (Lake Sipin and Lake Teluk) to compare abundance of aquatic insect larvae (family: Chironomidae). Lake Sipin located close by the settlement and got many influences from anthropogenic activities. However, Lake Teluk got less anthropogenic disturbance. Both lakes have difference plants cover. The area around Lake Sipin was more open compared to Lake Teluk and it caused low transparency level in Lake Sipin. The transparency level of Lake Sipin was 58.62 cm whereas transparency level of Lake Teluk was 70.29 cm. The difference of this transparency level influenced Chironomidae Larvae abundance that was encountered. Larvae abundance which was found in Lake Sipin was 49 ind/m2, while larvae abundance of Lake Teluk was 374 ind/m2. The result showed that water transparency level, water colors and vegetation affected abundance of Chironomidae larvae.